2020
DOI: 10.1016/j.sjbs.2019.10.006
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant, cytotoxic and antibacterial potentials of biosynthesized silver nanoparticles using bee’s honey from two different floral sources in Saudi Arabia

Abstract: Nowadays, the innovative study of silver nanoparticles (AgNPs) is excessive since they have incredible biomedical applications. The current study aimed to find out the potential of honey from two different floral sources (Ziziphus spina-christi and Acacia gerrardii) as biogenic mediators to synthesize AgNPs and to evaluate their antioxidant, cytotoxic and antimicrobial abilities. Biogenic AgNPs were studied for particle characterizations and the expected biomolecules helped in the reduction process of silver (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 51 publications
1
20
0
2
Order By: Relevance
“…In their study, lower IC 50 of 3.8 and 6.6 µg/mL were found compared with our results when they used AgNPs synthesized using Ganoderma lucidum and Phellinus igniarius respectively. Generally, anticancer activity of AgNPs prepared using green synthesis was well documented 16,35,58,88,89 . Further studies stated the IC 50 of AgNPs synthesized using biogenic extract were ranged between 10.9 to 21.4 against HepG2, LoVo, and MDA-MB 231cell 90 and another study showed IC 50 ranged between 35.15-56.73 μg/mL against a LoVo cell with 16 .…”
Section: Identification Of Lichens Secondary Metabolites By (Gc-ms)mentioning
confidence: 99%
“…In their study, lower IC 50 of 3.8 and 6.6 µg/mL were found compared with our results when they used AgNPs synthesized using Ganoderma lucidum and Phellinus igniarius respectively. Generally, anticancer activity of AgNPs prepared using green synthesis was well documented 16,35,58,88,89 . Further studies stated the IC 50 of AgNPs synthesized using biogenic extract were ranged between 10.9 to 21.4 against HepG2, LoVo, and MDA-MB 231cell 90 and another study showed IC 50 ranged between 35.15-56.73 μg/mL against a LoVo cell with 16 .…”
Section: Identification Of Lichens Secondary Metabolites By (Gc-ms)mentioning
confidence: 99%
“…The effect of floral origin and altitude on physiochemical properties and concentration of vitamins was analyzed by Al-Mosa et al, 2019 , Mohammed et al, 2019 . Many researchers worked on antimicrobial ( Abdallah and Hamed, 2019 , Al-Hindi and Shehata, 2014 , Ansari et al, 2017a , Ghramh et al, 2019a , Ghramh et al, 2019b , Owayss et al, 2019 ), antioxidant ( Al-Hindi and Shehata, 2014 ), physicochemical properties including some quality parameters ( Ahamed et al, 2017 , Alqarni et al, 2014 , Alqarni et al, 2016 , Mesallam and El-Shaarawy, 1987 , Osman et al, 2007 ), mineral contents ( Al-Hindi and Shehata, 2014 , Alqarni et al, 2014 , Arida et al, 2012 , Osman et al, 2007 , Taha et al, 2018 ), floral pigments ( Alqarni et al, 2016 ), heavy metals ( Bazeyad et al, 2019 ), validation of botanical origins and geographical sources through ultraviolet spectroscopy and chemo metric analysis ( Ansari et al, 2018 ), and formation and biological activities of nanoparticles by using honey samples ( Al-Brahim and Mohammed, 2020 , Ghramh et al, 2019b ). Most of the previous research on honey deals with the above-mentioned parameters rather than quantifying the two most important quality parameters (sucrose and HMF) present in honey samples.…”
Section: Introductionmentioning
confidence: 99%
“…Various routes are available in nanoparticles synthesis; they are physical, chemical, biological. Among these, biological route is considered more efficient than other routes due to the low toxicity, low cost, increased surface nature and volume zero ( Al-Brahim and Mohammed, 2020 ). Sometimes, the chemical mediated nanoparticles seriously affected the environment and others directly or indirectly due to the toxic nature ( Lakhan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%